PELAKSANAAN PERJANJIAN BAGI HASIL PERTANIAN LAHAN SAWAH: Studi di Kecamatan Gamping, Kabupaten Sleman, Yogyakarta - Unggul Priyadi; Jannahar Saddam Ash Shidiqie (Millah: Journal of Religious Studies, 2015)
Gamping Sub-district using Islamic Law. Data used in this study were obtained from interview, observation, and documentation. The collected data were tested their validity using data source triangulation and analyzed using Miles and Huberman model. The conclusion of this study are: The reason of paddy field owners in Gamping Sub-district to choose profit sharing scheme compared to rental scheme or paying farm workers in managing their fields because they want to enjoy the yields gradually and do not want to be involved directly in managing the paddy field. The agreement of profit sharing in Gamping Sub-district in general is conducted orally, based on trust, without any witnesses. The term is not defined clearly. The profit sharing balance is set since the first time of agreement. The balance of profit sharing used in general is “maro” (½ part for sharecroppers and ½ part for owner) with all the production costs borne by the sharecroppers, and the yields are immediately halved. In the event of crop failure, it becomes the risk borne by the sharecroppers. The paddy land tax is paid by the owner. The crop yields reaching specific nisab or limit in general are not directly paid for the zakat. The implementation of profit sharing agreement for paddy fields in Gamping Sub-district is not fully in accordance with the Islamic law because there is no socialization from any parties related to the Islamic Law in agricultural cooperation, here is hereditary habit, the owners and sharecroppers do not want to use the red tape and complicated procedure, the owners have been good enough and fair with the common system used, and the sharecroppers accept the habit in force although they feel that it is hard and unfair.